FEMININE PROSPECTIVE IN ANITA NAIR’S LESSONS IN FORGETTING - Venibha. P, Starlin Judith; D.L. Jaisy (International Journal of Psychosocial Rehabilitation, 2020)
Indian women novelists have given a new dimension to the Indian Literature. It reflects the hopes and aspirations of the people. Anita Nair has much insight into the concerns of studies, family, love and striving for fame and fortune. She has portrayed such a life in her recent novel lessons in forgetting. For modern educated women, marriage is the main problem. Lessons In forgetting is a depiction of characters due to failed marriages particularly the psychological conflicts. This fiction is impressive in its skill and painful in its Integrity. The novel deals with the life of upper middle class families of Nintees against the back drop of the Southern Tamil Nadu and Bangalore. In this novel the writer describe the whole world of women with simply stunning frankness. This article attempts to explore how aspirations and struggle help people to overcome from the predicament and to establish one’s identity.